2004
DOI: 10.1111/j.1468-2982.2004.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Postictal Headache in Patients with Partial Epilepsy

Abstract: Migraine-like features sometimes characterize the headache that follows epileptic seizure (postictal headache, PIH). We compared patients with different types of epilepsy to investigate the association between migraine-like PIH and seizure type. Subjects comprised 364 patients with partial epilepsy. Epilepsy types were temporal lobe epilepsy (TLE, n = 177), frontal lobe epilepsy (FLE, n = 116), and occipital lobe epilepsy (OLE, n = 71). Patients participated in a structured interview pertaining to PIH as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
68
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 30 publications
9
68
1
5
Order By: Relevance
“…Our results are close to the prevalence of 5-15% for pre-ictal headache that was reported in epilepsy and of especially 11% in pharmacologically refractory partial epilepsy (29)(30)(31). Similar to our findings, in the other studies, post-ictal headaches are more common than pre-ictal headaches which are often the migraine type and especially occur after some types of epilepsy such as generalized tonic-clonic and occipital lobe epilepsies (1,29,32,33). Limitations of this study were small sample size, prospective nature of the study and undifferentiated epileptic syndromes.…”
Section: Discussionsupporting
confidence: 80%
“…Our results are close to the prevalence of 5-15% for pre-ictal headache that was reported in epilepsy and of especially 11% in pharmacologically refractory partial epilepsy (29)(30)(31). Similar to our findings, in the other studies, post-ictal headaches are more common than pre-ictal headaches which are often the migraine type and especially occur after some types of epilepsy such as generalized tonic-clonic and occipital lobe epilepsies (1,29,32,33). Limitations of this study were small sample size, prospective nature of the study and undifferentiated epileptic syndromes.…”
Section: Discussionsupporting
confidence: 80%
“…These findings are in accordance with our study. Ito et al found somewhat lower numbers, 29% and 26% [4,10]. They also found an association between postictal and interictal migraine.…”
Section: Discussionmentioning
confidence: 92%
“…These findings support the hypothesis of a common pathophysiology for post-and interictal headache, and also that seizures may serve as one of several triggering factors for headache. It has been demonstrated that migraine-like postictal headaches occur more often with seizure onset in the posterior parts of the brain compared with frontal lobe onset [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of those with PIH ranges between 12% and 52% [3][4][5] , implying that PIH adds an additional significant burden to persons with epilepsy in addition to actual seizures. We have investigate the incidence of PIH and the factors potentially related to the occurrence of PIH in a Chinese epileptic center, from Feb. 01, 2012 to May 10, 2013, which based on the guideline of ICHD-II.PIH occurred in 328 (38%) of the subjects, and the incidence of PIH in occipital lobe epilepsy (OLE, 56%) was significantly higher than in temporal lobe epilepsy (TLE, 35%) and frontal lobe epilepsy (FLE, 39%).…”
Section: Introductionmentioning
confidence: 99%